Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1590/0001-3765201820180100
|View full text |Cite
|
Sign up to set email alerts
|

Sampling system for estimating woody debris in an urban mixed tropical forest

Abstract: Woody debris, defined as standing and downed deadwood, consists in an essential component of the forest carbon stock. However, few studies have been carried out to get an efficient and accurate sampling procedure for estimating it. This work proposes two methodologies to estimate the woody debris volume in a Brazilian mixed tropical forest: 1) two-stage systematic sampling, using a mixed methodology, in which the Strand's method is applied to standing dead trees and stumps, and line intercept sampling is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Previous studies showed that leaf litter and FWD were spatially autocorrelated with a range ≤5 m in planted pine forests (Penne et al, 2010). It has also been reported that the spatial distribution of CWD does not show spatial autocorrelation in tropical forests (Péllico et al, 2018). Collectively, these studies suggest that the spatial autocorrelation of DOM depends on topography, forest type, and DOM type.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies showed that leaf litter and FWD were spatially autocorrelated with a range ≤5 m in planted pine forests (Penne et al, 2010). It has also been reported that the spatial distribution of CWD does not show spatial autocorrelation in tropical forests (Péllico et al, 2018). Collectively, these studies suggest that the spatial autocorrelation of DOM depends on topography, forest type, and DOM type.…”
Section: Discussionmentioning
confidence: 87%